ANALYSIS OF THE TOURISTS’ OPINION CONCERNING THE INVESTMENTS IN THE DANUBE DELTA - Romeo Cătălin CREȚU; Petrică ȘTEFAN; Ioan Iulian ALECU; Silviu Viorel ANDREI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The Danube Delta is a poorly developed area, but it has tremendous potential. The European Union will allocate the Danube Delta by 2020, with the possibility of extending for an additional three years the amount of 1.3 billion euros for infrastructure, tourism and jobs. In this paper we analysed, based on the questionnaire, the opinion of the tourists who visited the Danube Delta regarding the future investments aimed at developing the Danube Delta reservation. The questionnaire was applied on a sample of 1,067 tourists, from 1 March 2017 to 31 January 2018, in the following localities: Crişan, Murighiol, Sulina, Mila 23, Sfântu Gheorghe, Caraorman, Periprava, Maliuc, Gorgova and Dunavăţu de jos. The tourists' opinion on the investments that should be made for the development of this area, 55% think that investments in road infrastructure should be made, 23% in actions to promote the tourist potential of this area, 15% consider it necessary investment in utility infrastructure, and 5% of them consider the number of tourist units to be insufficient.